2006
DOI: 10.1111/j.1445-5994.2006.01212.x
|View full text |Cite
|
Sign up to set email alerts
|

Information from the Internet: attitudes of Australian oncology patients

Abstract: Information searching is common in ambulatory Australian oncology patients, with the Internet being a frequently used resource. To ensure patients find reliable and relevant information and to minimize the risk of harm, health professionals involved in treating oncology patients should provide guidance in finding information sources and assistance in interpreting the information obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 23 publications
2
65
2
Order By: Relevance
“…We collected information as to whether Internet use influenced patients" decision in the areas of treatment, physician, and participation in clinical trials. One study showed that Internet searching adversely impacted the physician-patient relationship in 8% of surveyed patients [8], while another study did not find any impact [6]. Oncologists are aware of the prevalence of the Internet use by cancer patients, but most of them have neutral or even nihilistic feelings towards it [6,24].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We collected information as to whether Internet use influenced patients" decision in the areas of treatment, physician, and participation in clinical trials. One study showed that Internet searching adversely impacted the physician-patient relationship in 8% of surveyed patients [8], while another study did not find any impact [6]. Oncologists are aware of the prevalence of the Internet use by cancer patients, but most of them have neutral or even nihilistic feelings towards it [6,24].…”
Section: Discussionmentioning
confidence: 97%
“…The most common reason for searching the Internet (52.1%) in our study is to develop questions to discuss with physicians. Indeed, patients do seem to attempt to discuss the acquired information either with local doctors or specialists [8]. This may not be well- [24].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Gynecological cancer Internet is increasingly recognized as an important source of information. Several publications have reported the prevalence of internet use as a source of cancer information, recently reporting that 30-50% of patients use the Internet to search for information on their own health [1][2][3][4][5][6]. The percentage of internet users who search for health information has been stable in America over the past years [7].…”
mentioning
confidence: 99%
“…[15][16][17] Certain demographic groups of cancer survivors appear to seek information more frequently than others, namely those who are younger (<65 years of age), females, those on higher incomes and those who receive regular healthcare from the same provider(s). 18 Although desire for information and autonomy has been demonstrated to vary with such demographic features as well as with cultural norms, giving survivors worldwide the option to have further information seems universally indicated.…”
mentioning
confidence: 99%